Ottawa Model of Implementation Leadership and Implementation Leadership Scale: mapping concepts for developing and evaluating theory-based leadership interventions - Gifford W; Graham ID; Ehrhart MG; Davies BL; Aarons GA (Dove Medical Press, 2017)
Wendy Gifford,1 Ian D Graham,2,3 Mark G Ehrhart,4 Barbara L Davies,5,6 Gregory A Aarons7 1School of Nursing, Faculty of Health Sciences, University of Ottawa, ON, Canada; 2Centre for Practice-Changing Research, Ottawa Hospital Research Institute, 3School of Epidemiology, Public Health and Preventive Medicine, Facility of Medicine, University of Ottawa, Ottawa, ON, Canada; 4Department of Psychology, San Diego State University, San Diego, CA, USA; 5Nursing Best Practice Research Center, University of Ottawa, Ottawa, ON, Canada; 6Department of Psychiatry, University of California, San Diego, La Jolla, CA, USA; 7Child and Adolescent Services Research Center, University of California, San Diego, CA, USA Purpose: Leadership in health care is instrumental to creating a supportive organizational environment and positive staff attitudes for implementing evidence-based practices to improve patient care and outcomes. The purpose of this study is to demonstrate the alignment of the Ottawa Model of Implementation Leadership (O-MILe), a theoretical model for developing implementation leadership, with the Implementation Leadership Scale (ILS), an empirically validated tool for measuring implementation leadership. A secondary objective is to describe the methodological process for aligning concepts of a theoretical model with an independently established measurement tool for evaluating theory-based interventions.Methods: Modified template analysis was conducted to deductively map items of the ILS onto concepts of the O-MILe. An iterative process was used in which the model and scale developers (n=5) appraised the relevance, conceptual clarity, and fit of each ILS items with the O-MILe concepts through individual feedback and group discussions until consensus was reached.Results: All 12 items of the ILS correspond to at least one O-MILe concept, demonstrating compatibility of the ILS as a measurement tool for the O-MILe theoretical constructs.Conclusion: The O-MILe provides a theoretical basis for developing implementation leadership, and the ILS is a compatible tool for measuring leadership based on the O-MILe. Used together, the O-MILe and ILS provide an evidence- and theory-based approach for developing and measuring leadership for implementing evidence-based practices in health care. Template analysis offers a convenient approach for determining the compatibility of independently developed evaluation tools to test theoretical models. Keywords: leadership, implementation, evidence-based practice, template analysis, theoretical models, leadership development, knowledge translation